Characteristics and Thermal Kinetics of Hydroxyapatite Crystals Doped with Tricarballylic Acid. Issue 6 (14th March 2018) - Polat, Sevgi; Sayan, Perviz
Abstract: Hydroxyapatite (HAP) has attracted interest in many fields, e.g., catalysis, water treatment processes, and pharmaceutical industries. HAP crystallization was performed within a batch‐type crystallizer both with and without tricarballylic acid used as additive. The crystals produced in pure media and in the presence of tricarballylic acid were characterized and their thermal degradation was then accomplished in a thermal analyzer in an inert atmosphere. Experimental data was used to calculate the activation energies based on the Kissinger, Flynn‐Wall‐Ozawa, Kissinger‐Akahira‐Sunose, and Starink kinetic models. The results revealed that tricarballylic acid was adsorbed onto the crystal surface, with significant effects on crystal morphology, thermal degradation behavior, and average activation energy. Abstract : The effects of tricarballylic acid on the crystallization characteristics of hydroxyapatite were studied in a comprehensive manner. Detailed thermal degradation kinetic modeling was performed by using various types of model‐free kinetic isoconversional methods, demonstrating that tricarballylic acid is a potential additive for hydroxyapatite crystallization.